2021
DOI: 10.46245/ijorer.v2i2.93
|View full text |Cite
|
Sign up to set email alerts
|

The Problem Based Learning in Enhancing Students’ Critical Thinking for Reading Skills in English Teaching at Vocational School

Abstract: The purpose of this research explained how Problem Based Learning (PBL) designed in teaching and learning English for Vocational School students in Indonesia. A PBL was used for overcoming critical thinking skill in teaching English at vocational school. The sample consisted of tenth grade of vocational school students who were recruited purposively. The research methodology used qualitative and qualitative method. Interview was used to get data about instructional and students’ needs. Questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Based on the description above, it can be concluded that the Reciprocal Teaching model is an alternative that can be used in improving students' mathematical communication skills (Iskandar, Jannah, & Wicaksono, 2021), especially the material on relations and functions at the Milk Base National Development Junior High School (Kilelu, van der Lee, Koge, & Klerkx, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the description above, it can be concluded that the Reciprocal Teaching model is an alternative that can be used in improving students' mathematical communication skills (Iskandar, Jannah, & Wicaksono, 2021), especially the material on relations and functions at the Milk Base National Development Junior High School (Kilelu, van der Lee, Koge, & Klerkx, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It can be said that a foreign language is a necessity and life essence that becomes a basic provision in living life (Purwono, 2021;Purwono & Asteria, 2021). Furthermore, learning and mastering foreign languages can also be a means to improve one's own abilities, understand other cultures, build an attitude of self-initiative, be able to adapt and interact in teams from different language and cultural backgrounds, and be able to be open-minded and broadminded (Bin & Mandal, 2019;Nurul Iskandar et al, 2021). English is an International language that is used by all countries in the world in all matters between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to this statement, in particular, learning English at the primary school level is basically a process of interaction between students and their environment, with their teachers, with their peers in the same goal, namely to master English, so mastering English will be a provision for a better life in the future. Furthermore, English language learning is often considered as a translation of the term "instructional", which is the process of interaction of learners with educators and learning resources in a learning environment (Nurul Iskandar et al, 2021;Rohqim, 2020). English language learning in primary schools is identified as an effort that aims to help learners at the primary school level understand English.…”
Section: Introductionmentioning
confidence: 99%
“…The 4C skills and innovations of 21st-century learning are applied to prepare Indonesia's young generation to survive and compete in the 21st century. That is, teachers must be innovative in preparing students for the demands of 21st-century skills (Iskandar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%